Building microservices with Clojure and Pedestal : a practical introduction to tooling, development, and deployment - Rehordn, Scott; Safari eBooks ([Place of publication not identified] : O'Reilly, 2015)
"In this Building Microservices with Clojure and Pedestal training course, expert author Scott Rehorn will teach you how to set up, modify, and deploy a basic microservice based on Clojure and Pedestal. This course is designed for users that already have programming experience. You will start by learning about the stack and toolchain, then jump into using Pedestal. From there, Scott will teach you how to use Pedestal as a web services framework to handle request and response routing and content handling. This video tutorial also covers persistence, how to protect your endpoints with a simple API key strategy, and how to use XML in Clojure. Finally, you will learn about Java Interop. Once you have completed this computer based training course, you will be fully capable of setting up, modifying, and deploying a microservice with Clojure and Pedestal."--Resource description page.
Title from title screen (viewed August 24, 2015).
Date from resource description page.
Presenter, Scott Rehorn.
Keywords: Computer architecture; Clojure (Computer program language); Functional programming languages; Distributed operating systems (Computers); Computer software -- Development; Electronic books